Clinical manifestation of neonatal sepsis and prevalence of ESBL-producing bacteria in South Asia - Ashraf, Wakia Shams; Munira, Mehraj Noor; Tabassum, Sadia (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology and Bachelor of Science in Microbiology, 2023.